Kasdienė refleksija ir filosofo refleksijos radikalumas - Tuzova, Tamara (Problemos, 2004)
The object of the investigation is the specificity of philosophical and everyday reflections, their interrelations. The author makes an attempt to reveal the invariant constitutive characteristics of the structure of the reflective space of philosophy, to define the sense of specific radicalism of philosophical reflection. The radicalism as effort and way to extend presence of us in one’s own experience and as self-aware transformation of own experience which presuppose the unity of the factual and the due as possible (and necessary) for man is revealed. The variant of the “metaphysics of presence” of man in the objects and relations of his experience as the way of historical and logical identification of philosophical reflection is developed. The “metaphysics of presence” is introduced as common dimension of the intelligibility, which permits the author to compare competitive modes of reflection of human experience (reductive and nonreductive, deterministic and transcendental) and to interpret them as irreplaceable and mutually supplementary ways of broadening the limits of self-consciousness of human experience.